Characteristics and Clinical Implications of the Nasal Microbiota in Extranodal NK/T-Cell Lymphoma, Nasal Type - Shi, Zhuangzhuang; Li, Xin; Wang, Xinhua; Zhang, Lei; Li, Ling; Fu, Xiaorui; Sun, Zhenchang; Li, Zhaoming; Zhang, Xudong; Zhang, Mingzhi (Frontiers in Cellular and Infection Microbiology, 2021)
Natural killer/T cell lymphoma (NKTCL) most frequently affects the nasal cavity and upper aerodigestive tract (UAT) and is often mistaken for reactive disease processes, such as chronic rhinosinusitis (CRS). Recently, alterations of the nasal resident microbiota have been found in CRS. However, nasal microbial features in NKTCL have never been reported. This case-control study collected 46 NKTCL patients, 25 CRS patients and 24 matched healthy controls (HCs) to analyze nasal microbial profiles via 16S rRNA sequencing technology to improve our understanding of changes in the nasal microbiota in NKTCL. We found that alpha diversity was significantly decreased, while beta diversity was significantly increased in NKTCL compared with those in CRS and HCs. The genus Corynebacterium was significantly depleted in CRS and NKTCL versus that in HCs, while genus Staphylococcus was the most abundant in the NKTCL compared to that in the other two groups. The nasal microbial community was significantly different between UAT-NKTCL and non-UAT NKTCL patients. Importantly, based on a panel of taxa, excellent classification power with an AUC of 0.875 between UAT-NKTCL and CRS was achieved. Furthermore, the alpha diversity of the nasal microbiota was associated with several clinical covariates of NKTCL. Finally, PICRUSt analysis implicated an array of distinct functions in NKTCL that might be involved in the pathogenesis of the disease. In conclusion, the nasal microbial profile was unique in NKTCL. The nose-microbiota-UAT NKTCL axis represents a panel of promising biomarkers for clinical practice and contributes to revealing the potential pathogenesis of this malignancy.